Advances in Food Processing (Food Preservation, Food Safety, Quality and Manufacturing Processes) (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This e-book aims to compile advances in the area of food manufacturing including packaging to address issues of food safety, quality, fraud, and how these processes (new or old) could affect the organoleptic characteristics of foods, with the aim to promote consumers’ satisfaction. Moreover, food supply issues are explored. New and improved technologies are employed in the area of food manufacturing to address consumer needs in terms of quality and safety. The issues of research and development should be taken into account seriously before launching a new product onto the market. Finally, food fraud and authenticity are very important issues, and the food industry should focus on addressing them.